PREDICTION OF HIV PREVALENCE AMONG INDIVIDUALS AGED 15-49 YEARS IN LATIN AMERICA AND THE CARIBBEAN USING HOLT’S LINEAR METHOD (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Latin America and the Caribbean from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue on an upward trend over the out of sample period. Therefore, it is important to address main drivers of HIV transmission in the region targeting adolescents, men who have sex with other men and commercial sex workers. Moreover, it is essential to ensure ART treatment adherence among young adults living with HIV to minimize emergence of drug-resistant HIV strains and control HIV spread.